Chlorophytum borivillianumbaker: a Potent Medicinal Plant - Yadava, Anil Kumar; Pandey, Rakesh (Indian Forester, 2004)
The paper describes the cultivation package of Chlorophytum borivillianum Baker and economic of cultivation of the species on commercial scale.